2008
DOI: 10.1108/14636680810918478
|View full text |Cite
|
Sign up to set email alerts
|

The great gas pipeline game: monopolistic expansion of Russia's Gazprom into European markets

Abstract: PurposeRussian dominance of the Eurasian natural gas delivery system has put the independence of the EU's foreign policy at risk. Although Europe is struggling to counteract the threat, Russia appears to be winning the game. This paper aims to recommend significant measures to reverse the trend.Design/methodology/approachThis is a discussion paper exploring the issues involved.FindingsRussia's stranglehold already has acquired 25 percent of the European market. Moreover, it is installing four new pipelines, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Previous research has already shown that the "great natural gas pipeline game" can be won (Schaffer 2008), but only by acting with rapid commitment. Hopefully commerce is not taking back seat to politics (Freifeld 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has already shown that the "great natural gas pipeline game" can be won (Schaffer 2008), but only by acting with rapid commitment. Hopefully commerce is not taking back seat to politics (Freifeld 2009).…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in Fig. 1 (left), European gas consumption will grow-largely due to increased gas-fired power generation (Bothe and Lochner 2008;Kjärstad and Johnsson 2007)-from approximately 500 bcm in 2005, valued at about USD 100 billion (Schaffer 2008), to about 816 bcm in 2030 (OME 2006) representing an average growth rate of 2% per annum. 1 As the indigenous gas production of the European Union declines (BCG 2005), a growing gap between gas production and gas demand-as illustrated by Fig.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations